2015
DOI: 10.1371/journal.pone.0123850
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Dependent Changes in the Regional Amplitude and Synchronization of Resting-State Functional MRI in Stroke

Abstract: Resting-state functional magnetic resonance imaging (R-fMRI) has been intensively used to assess alterations of inter-regional functional connectivity in patients with stroke, but the regional properties of brain activity in stroke have not yet been fully investigated. Additionally, no study has examined a frequency effect on such regional properties in stroke patients, although this effect has been shown to play important roles in both normal brain functioning and functional abnormalities. Here we utilized R-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
34
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 38 publications
13
34
2
Order By: Relevance
“…In addition, several studies (Park et al, 2011;Yin et al, 2014;Yin, Luo, et al, 2013a) have influenced the robustness of their results. Interestingly, we did not find increased ReHo in the parietal cortex in the patient group, which was a primary outcome reported in Zhu's study (Zhu et al, 2015), in the comparisons between the HC group and the patient group (CPH + PPH, 52 patients) in the three frequency bands. Interestingly, we did not find increased ReHo in the parietal cortex in the patient group, which was a primary outcome reported in Zhu's study (Zhu et al, 2015), in the comparisons between the HC group and the patient group (CPH + PPH, 52 patients) in the three frequency bands.…”
Section: Frequency-specific Changes In Reho Between the Two Subgroupscontrasting
confidence: 52%
See 1 more Smart Citation
“…In addition, several studies (Park et al, 2011;Yin et al, 2014;Yin, Luo, et al, 2013a) have influenced the robustness of their results. Interestingly, we did not find increased ReHo in the parietal cortex in the patient group, which was a primary outcome reported in Zhu's study (Zhu et al, 2015), in the comparisons between the HC group and the patient group (CPH + PPH, 52 patients) in the three frequency bands. Interestingly, we did not find increased ReHo in the parietal cortex in the patient group, which was a primary outcome reported in Zhu's study (Zhu et al, 2015), in the comparisons between the HC group and the patient group (CPH + PPH, 52 patients) in the three frequency bands.…”
Section: Frequency-specific Changes In Reho Between the Two Subgroupscontrasting
confidence: 52%
“…Third, we explored the correlations between ReHo values at the specific frequency bands and the FMA-HW scores of hand function across all the stroke patients. Based on the typical frequency band studies among stroke subgroups (Yin, Luo, et al, 2013a;Yin et al, 2012Yin et al, , 2014 and a subfrequency study between stroke patients and HCs (Zhu et al, 2015), we hypothesized that spontaneous brain activity following stroke would be influenced by both the specific frequency of LFO and the severity of stroke. We predicted that the results in the typical band would be consistent with those of our previous studies among stroke subgroups, which might be found in the primary sensorimotor cortex, SMA, and several high-order motor regions, such as the frontal gyrus and the parietal lobule.…”
mentioning
confidence: 99%
“…3 and 6). This observation is in accordance with a previous report describing a high susceptibility of those slow-5 oscillations after the event of a stroke and the contribution of those oscillations to the cortical impairment (Zhu et al, 2015).…”
Section: Discussionsupporting
confidence: 94%
“…6), which is consistent with studies found in the literature (Garrity et al, 2007;Zuo et al, 2010). In contrast, our population of subacute stroke patients displayed a reduction in the amplitude and power that was specific to those slow-5 oscillations, which is consistent with results of a recent report by Zhu et al (2015), where more activity changes were recorded in the ALFF of the slow-5 band. Our observation is coupled with an increase in slow-4 oscillations.…”
Section: Implications Of Slow-5 Oscillation Powersupporting
confidence: 93%
See 1 more Smart Citation